The Portuguese Colonial War and the African Liberation Struggles Memory, Politics and Uses of the Past - Cardina, Miguel (Memory Studies: Global Constellations, 2024)
The Portuguese Colonial War and the African Liberation Struggles: Memory, Politics and Uses of the Past presents a critical and comparative analysis on the memory of the colonial and liberation wars that led to a regime change in Portugal and to the independence of five new African countries: Angola, Mozambique, Guinea-Bissau, Cape Verde and São Tomé and Príncipe.　 Covering more than six decades and based on original archival research, critical analysis of sources and interviews, the book offers a plural account of the public memorialization of this contested past in Portugal and in former colonized territories in Africa, focusing on diachronic and synchronic processes of mnemonic production. This innovative exercise highlights the changing and crossed nature of political memories and social representations through time, emphasizing three modes of mnemonic intersections: the intersection of distinct historical times; the intersection between multiple products and practices of memory; and the intersection connecting the different countries and national histories. The Portuguese Colonial War and the African Liberation Struggles: Memory, Politics and Uses of the Past is the major and final output of the research developed by CROME - Crossed Memories, Politics of Silence, a project funded by a Starting Grant (715593) from the European Research Council (ERC). The book advances current knowledge on Portugal and Africa and deepens ongoing conceptual and epistemological discussions regarding the relationship between social and individual memories, the dialectics between memory, power and silence, and the uses and representations of the past in postcolonial states and societies.